Strategi Dakwah Dalam Membangun Kesadaran Masyarakat Akan Urgensi Pembayaran Zakat - Nasution, Siti Arbiah (Jurnal Dakwah dan Masyarakat, 2025)
Public awareness plays a crucial role in helping zakat managers effectively distribute zakat to those in need. To maximize the goals of da'wah, it is essential to have a well-planned strategy that outlines specific actions and efforts tailored to the unique context or environment. This study employs a descriptive and qualitative approach, using methods such as observation, interviews, and documentation to gather data. The da'wah strategy implemented by Baznas Kota Sungai Penuh focuses on engaging the community through family-oriented approaches, face-to-face interactions, and the use of social media. Consistent and comprehensive zakat outreach is vital to enhance understanding among the public, facilitating the smooth collection of zakat funds and fostering stronger relationships. The effective collection of zakat is key to improving the economic well-being of mustahik. Additionally, the process of zakat collection helps purify the minds of the muzakki, encouraging a deeper appreciation for sincerity in giving. Overall, raising awareness about zakat is essential in strengthening ukhuwah among individuals Abstrak Kesadaran masyarakat terhadap pengumpulan zakat memiliki peran penting dalam mempermudah pengelola zakat untuk menyalurkannya kepada mustahik. Untuk dakwah akan tercapai secara maksimal, diperlukan strategi dakwah yang terstruktur, mencakup cara dan langkah-langkah yang disesuaikan dengan kondisi dan lingkungan tertentu. Penelitian ini menggunakan metode deskriptif kualitatif, dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Baznas Kota Sungai Penuh menerapkan strategi dakwah berupa pendekatan keluarga, interaksi langsung, serta pemanfaatan media sosial untuk meningkatkan sosialisasi zakat. Penyuluhan yang berkelanjutan mengenai zakat sangat diperlukan agar masyarakat dapat lebih memahami zakat, sehingga proses pengumpulan dana zakat berjalan dengan baik dan hubungan sosial semakin erat. Pengumpulan zakat juga berperan penting dalam mendukung ekonomi para mustahik. Selain itu, zakat yang terkumpul dapat membantu menyucikan hati dan pikiran, serta mengajarkan pentingnya keikhlasan kepada para muzakki. Pemahaman tentang zakat yang mendalam turut mempererat ukhuwah antar sesama.